NAVIGATING AI-ASSISTED ACADEMIC WRITING: UNIVERSITY STUDENTS’ PERSPECTIVES AND CHALLENGES - Ahmad Sani, Fatin Rahaina; Md Tahir, Norlizawati; Jahaya, Nadira M.; Morat, Berlian Nur (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
The growing use of artificial intelligence (AI) tools in academic writing is transforming how university students approach their assignments. These technologies offer numerous advantages, including enhanced language accuracy, improved clarity, and time efficiency. However, they also raise important concerns about academic integrity, over-reliance, and the development of independent writing skills. This study investigates university students’ perspectives on AI-assisted academic writing, aiming to understand their experiences, perceived benefits, challenges, and future intentions. Data was collected through qualitative interviews using Google Forms, involving university students across various academic disciplines. Thematic analysis revealed several key patterns: ChatGPT, QuillBot, and Grammarly were the most frequently used tools, mainly for grammar correction, paraphrasing, and idea generation. Many students reported increased confidence and clarity in their writing, with AI tools becoming integrated into their writing routines. Nevertheless, concerns were expressed regarding citation accuracy, misinformation, ethical use, and a growing dependence on AI-generated suggestions. Despite these limitations, most participants expressed intentions to continue using AI tools, particularly as aids for editing and organizing ideas rather than for full content generation. The findings provide valuable insights for educators and academic institutions seeking to support responsible AI integration in higher education. This study highlights the need for a balanced approach to AI use that promotes technological literacy alongside critical thinking and independent writing development.